Half lives - Grant, Sara, 1968- (Little, Brown and Company, 2013)
Follows the lives of two unlikely teenaged heroes, mysteriously linked and living hundreds of years apart, as both struggle to survive and protect future generations from the terrible fate that awaits any who dare to climb the mountain.